Analisis Manajemen Risiko Pada UMKM “Singkong Keju Mang Yudi” - Nuraisyah, Elza (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk management is a crucial element in maintaining and developing the Mang Yudi Cheese Cassava business amidst competitive market competition. The main objective of implementing risk management is to identify, assess and control various potential risks that could disrupt business operations and profits. Identified risks include operational risks, such as production disruptions and raw material availability; financial risks, such as cost fluctuations and unstable cash flows; marketing risks, including changes in consumer preferences and demand; as well as risks of compliance with health and food safety regulations. Through qualitative and quantitative risk analysis, each risk is evaluated based on its probability of occurrence and its impact on the business. The results of the analysis are used to determine effective mitigation strategies, such as supply chain optimization, appropriate financial management, and adaptive marketing innovation. The implementation of this risk management is expected to be able to maintain the stability and growth of Mang Yudi's Cassava Cheese business in the long term. SWOT analysis is used to provide a comprehensive picture of the strengths, weaknesses, opportunities and threats faced by a business. The main strengths include product quality and customer loyalty, while weaknesses include limited capital and production capacity.